Implementasi Pembelajaran Diferensiasi, Sosial dan Emosional dengan Media Pembelajaran Interaktif Si Peri Cantik - Wulandari, Tia Ratna (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to implement social and emotional-based differentiated learning using the interactive learning media SI PERI CANTIK for teaching plant parts and photosynthesis in fourth-grade elementary school students. The research employed a qualitative descriptive approach through observation, interviews, and documentation. The findings indicate that differentiated learning supported by SI PERI CANTIK significantly enhances student participation and teacher engagement. Both teacher and student activities were categorized as excellent, and student assessment results reflected improved conceptual understanding and numeracy literacy. Moreover, the approach contributed to the development of students’ social skills and digital literacy. The interactive media proved effective in delivering complex content visually and communicatively. This study contributes to the advancement of adaptive and contextual learning models in elementary education. Future research is recommended to examine the sustainability of this learning approach across various subjects and educational levels.